2006
DOI: 10.1515/jpem.2006.19.9.1113
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hidden Y Mosaicism in Turner's Syndrome: Importance in the Prevention of Gonadoblastoma

Abstract: A systematic search for hidden Y chromosome mosaicism in patients with TS and 45,X karyotype is justified by the possibility of developing gonadoblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 29 publications
3
50
0
16
Order By: Relevance
“…Thus, the use of molecular methods for identifying Y-chromosome-specific sequences has become an indispensable tool for detecting hidden mosaicism. [31][32][33][34] Nazarenko et al 35 also observed that cytogenetic analysis may not provide precise information on the presence of chromosomal mosaicism in patients with TS. Additional analysis of cells from tissues of different embryonic origins (mesodermal lymphocytes and ectodermal oral epithelium cells, for instance) allowed greater precision in defining the cytogenetic diagnosis.…”
Section: Detection Of Mosaicismmentioning
confidence: 99%
“…Thus, the use of molecular methods for identifying Y-chromosome-specific sequences has become an indispensable tool for detecting hidden mosaicism. [31][32][33][34] Nazarenko et al 35 also observed that cytogenetic analysis may not provide precise information on the presence of chromosomal mosaicism in patients with TS. Additional analysis of cells from tissues of different embryonic origins (mesodermal lymphocytes and ectodermal oral epithelium cells, for instance) allowed greater precision in defining the cytogenetic diagnosis.…”
Section: Detection Of Mosaicismmentioning
confidence: 99%
“…1,3,9,10 Today, there is no consensus regarding the need to systematically look for Y material in Turner's syndrome cases with the 45,X karyotype, given the possibility of gonadoblastoma development. 11 Therefore, FISH takes on a very important role in identifying such cases. 5,12,13 Although further studies are needed in order to define the precise risk of gonadoblastoma development in cases of 45,X/46,XY mosaicism, 9 patients with Turner's syndrome or Y mosaicism should have their gonads removed because fertility is not an issue, surgery presents low risk, and there is potentially a high risk of malignant degeneration in gonadic bands.…”
Section: 2mentioning
confidence: 99%
“…Embora ainda controverso (53), nessas pacientes, o risco de câncer está associado, principalmente, à presença do cromossomo Y, íntegro ou não, que pode levar ao desenvolvimento de gonadoblastoma e/ou disgerminoma nas gônadas disgenéticas (55).…”
Section: Hormônio De Crescimento E Síndrome De Turnerunclassified